Metastatic lobular carcinoma of the breast only in cystic lymph nodes, an incidental finding after laparoscopic cholecystectomy- A case report - Alipour, Sadaf; Eslami, Bita; Omranipour, Ramesh; Tavakol, Mahsa; Talebpour, Atieh (Current problems in cancer. Case reports, 2025)
Breast invasive lobular carcinoma (ILC) can metastasize to unusual sites due to a mutation in a cell-adhesion molecule called E-cadherin. The gastrointestinal tract (GI) and gallbladder (GB) are among these sites. Herein, we report a 62-year-old woman with a history of non-metastatic ILC who underwent laparoscopic cholecystectomy five years after her breast cancer diagnosis because of episodes of biliary colic. Pathology results revealed metastasis originating from the breast in two cystic lymph nodes, with a normal gallbladder. After cholecystectomy, a PET-CT scan was performed for restaging, which showed no other sites of metastasis, and only some nonspecific uptakes were reported in the skeletal system. This case highlights the possibility of unusual GI metastasis in patients with a history of breast cancer, especially ILC with GI symptoms, even when imaging appears normal.